Process Evaluation of Practice-based Diabetes Prevention Programs: What Are the Implementation Challenges?. (June 2015) - Carroll, Jennifer; Winters, Paul; Fiscella, Kevin; Williams, Geoffrey; Bauch, Jean; Clark, Linda; Sutton, James; Bennett, Nancy
Purpose: The purpose of this report is to describe lessons learned about the feasibility of recruitment and implementation of low-income adults with prediabetes in primary care clinics into diabetes prevention programs. Methods: Mixed methods process evaluation of a pragmatic 2-group pilot comparative effectiveness study of a community-developed Healthy Living Program (HLP) and a Diabetes Prevention Program (DPP) with 58 adults. Results: Of the total (n = 1215) assessed for eligibility, 7% (n = 92) were randomized, 58 completed the baseline assessment, and 31 completed the intervention. The process evaluation identified difficulty in systematically screening potentially eligible patients. There were several logistic and staffing challenges with program planning and initial start-up. Conclusions: Addressing challenges to feasibility is required for successful translation of evidence-based programs to clinical settings.